2018
DOI: 10.1093/cvr/cvy186
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib improves cardiac fibrosis but leaves pulmonary vascular remodelling unaltered in experimental pulmonary hypertension

Abstract: Nintedanib inhibits proliferation of pulmonary MVECs from controls, but not from PAH patients. While in rats with experimental PH nintedanib has no effects on the pulmonary vascular pathology, it has favorable effects on right ventricular remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 40 publications
0
37
0
Order By: Relevance
“…Additionally, it has been reported that BIBF1000, a structural precursor of nintedanib, did not disturb RV function in rats subjected to mechanical pressure overload by pulmonary artery-banding (42). Another recent study also showed that less dilatation, decreased fibrosis and hypertrophy of right ventricle after chronic treatment with nintedanib in Su/Hx-PAH rat by echocardiography and histological analysis (43), suggesting no cardiac toxicity of nintedanib.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, it has been reported that BIBF1000, a structural precursor of nintedanib, did not disturb RV function in rats subjected to mechanical pressure overload by pulmonary artery-banding (42). Another recent study also showed that less dilatation, decreased fibrosis and hypertrophy of right ventricle after chronic treatment with nintedanib in Su/Hx-PAH rat by echocardiography and histological analysis (43), suggesting no cardiac toxicity of nintedanib.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, Huang et al reported that chronic treatment with nintedanib reduced pulmonary vascular remodeling in the Fos-related antigen-2 mouse model of systemic sclerosis (46), which was supportive of our results. On the other hand, another more recent study showed that chronic treatment with nintedanib of established late-phase PAH, from 8 to 11 weeks, did not improved pulmonary hemodynamics and vascular remodeling in SuHx rats (43). The results of these recent studies of established animal and human PAH suggest that the therapeutic power of nintedanib may be limited at least in advanced stages of PAH.…”
Section: Discussionmentioning
confidence: 97%
“…The beneficial effects of carvedilol (β-blocker), iloprost (prostacyclin) and losartan (angiotensin receptor blocker) on RV function in animals are partly ascribed to attenuated TGF-β-mediated fibrosis [ 53 , 54 , 129 ]. Furthermore, nintedanib, a tyrosine kinase inhibitor known to inhibit TGF-β-mediated fibrosis, attenuated cardiac fibrosis in experimental pulmonary hypertension [ 130 , 131 ]…”
Section: Tgf-β Signaling In the Heart In Pulmonary Arterial Hypertmentioning
confidence: 99%
“…A recent experiment in rats showed that nintedanib reduced fibrosis and improved RV function, despite having no significant effects on the pulmonary vasculature. 18 Lastly, for advanced PAH, novel interventional techniques such as RV assist devices, devices to improve pulmonary arterial compliance, and advances in balloon septostomy are being explored as options for bridging to transplantation.…”
Section: Novel Therapies Targeting the Right Ventriclementioning
confidence: 99%